2011
DOI: 10.1074/jbc.m110.191411
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and Specificity Determinants of the Human Cbx Chromodomains

Abstract: The eight mammalian Cbx proteins are chromodomain-containing proteins involved in regulation of heterochromatin, gene expression, and developmental programs. They are evolutionarily related to the Drosophila HP1 (dHP1) and Pc (dPc) proteins that are key components of chromatin-associated complexes capable of recognizing repressive marks such as trimethylated Lys-9 and Lys-27, respectively, on histone H3. However, the binding specificity and function of the human homologs, Cbx1–8, remain unclear. To this end we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

22
388
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(412 citation statements)
references
References 39 publications
22
388
1
1
Order By: Relevance
“…Since H3K27me3 and H3K9me3 levels were concomitantly reduced at ERVs in Setdb1 knockout PGCs, deposition of the former may depend on the presence of the latter in such regions. Several members of the Cbx protein family interact with the core Polycomb-repressive complex 1 (PRC1), which promotes deposition of H3K27me3 by PRC2/EZH2, and a subset of these chromodomain proteins (CBX4, for example) has relatively high affinity for H3K9me3 (Vermeulen et al 2010;Kaustov et al 2011). Similarly, the chromodomain protein CDYL, which binds with high affinity to H3K9me3 (Vermeulen et al 2010) and directly recruits EZH2 (Zhang et al 2011), is highly expressed in PGCs.…”
Section: Discussionmentioning
confidence: 99%
“…Since H3K27me3 and H3K9me3 levels were concomitantly reduced at ERVs in Setdb1 knockout PGCs, deposition of the former may depend on the presence of the latter in such regions. Several members of the Cbx protein family interact with the core Polycomb-repressive complex 1 (PRC1), which promotes deposition of H3K27me3 by PRC2/EZH2, and a subset of these chromodomain proteins (CBX4, for example) has relatively high affinity for H3K9me3 (Vermeulen et al 2010;Kaustov et al 2011). Similarly, the chromodomain protein CDYL, which binds with high affinity to H3K9me3 (Vermeulen et al 2010) and directly recruits EZH2 (Zhang et al 2011), is highly expressed in PGCs.…”
Section: Discussionmentioning
confidence: 99%
“…Using histone peptides, it was shown that a conserved aromatic cage within the CD binds methylated H3K9 with low (micromolar) affinity but high sequence specificity and a preference for the trimethylated states (7)(8)(9). However, biochemical work on individual HP1 domains, HP1 proteins of different species and isoforms, has suggested that the CD might not be sufficient for HP1 nucleosome binding but that the hinge region or CSD make major contacts (10).…”
mentioning
confidence: 99%
“…These CBX proteins recruit PRC1 complex onto PRC2-enriched chromatin, facilitating the monoubiquitylation. The PRC1-dependent monoubiquitylation at Lys119 of histone H2A correlates with transcriptional repression (6)(7)(8)(9). This process is carried out by a heterodimeric RING finger E3 ligase, whose subunit binding the E2 ligase is RING1B, or its paralog RING1A.…”
mentioning
confidence: 99%